Identifikasi Kecenderungan Bakat dan Pengaruhnya Terhadap Hasil Belajar Mahasiswa Bimbingan dan Konseling - Mudaim Mudaim; Agus Wibowo (Universitas Mathla'ul Anwar Banten, 2018)
TALENT TRENDS IDENTIFICATION AND THE EFFECT ON LEARNING OUTCOMES OF GUIDANCE AND COUNSELING STUDENTS. The success of the learning process undertaken by individuals is not only determined by a single factor. Learning is a mental process, therefore identification of the influence of mental state is something very important. The mental aspect that allegedly influences individual learning outcomes is potential; talent. The purpose of this research is to identify student talent so that lecturers can do the learning process by taking into account individual differences, potentials and talents. This research was conducted at Muhammadiyah University of Metro. The population is all students of Guidance and Counseling University of Muhammadiyah Metro and the sample is determined by stratified random sampling. The research instrument uses talent test and student learning outcomes in the form of KHS. Analysis of correlational data using product moment. The results showed scholastic talent and student learning outcomes Guidance and Counseling University Muhammadiyah Metro is in the medium category. The contribution of scholastic talent to learning result or achievement index is 55,5%. and the correlation is 0.747 with sig.0.00.